Development of an Integrated Monitoring System for Temperature, Air Humidity, Soil Moisture, and Light Intensity in Measurement Aids in Secondary Schools - Afriani, Melly; Hamdani, Dedy; Putri , Desy Hanisa (Edukasi, 2024)
responses to monitoring system media, and to assess students' learning outcomes after utilizing these media. The research method used is the Research and Development (R&D) method, using the ADDIE model, which includes five phases Analyze, Design, Development, Implementation, and Evaluation. The subjects of this study consisted of 36 students in class X at SMA N 06 Bengkulu City. Data collection tools used in this study are questionnaires and tests of students' concept understanding. Data analysis techniques using a Likert scale with a scale of four.The results of the analysis stage showed that 77.8% of students agreed with development of learning media that has been designed. Development stage resulted in a validation score of 87.5% from the evaluator, which was categorized as very feasible. The student response to the media showed a percentage of 80.3%. The post-test results showed an average score of 84.16, with an average percentage score of 84%, categorized as good. This conclusion aims to evaluate students' conceptual understanding and responses, showing that instructional media can help students' conceptual understanding.